PENGARUH EDUKASI MEDIA BROADCAST WHATSAPP TERHADAP PENGETAHUAN PASIEN PROLANIS TENTANG PENCEGAHAN RISIKO KOMPLIKASI DIABETES MELITUS : Studi di Puskesmas Babakan Tarogong - Ulhaq, Dea Nabilah Dhiya' (Jurnal Kesehatan Siliwangi, 2024)
Background: In 2022, diabetes mellitus patients in the Babakan Tarogong Community Health Center area rose from 782 to 788, with 304 receiving standard health services. Based on the Indonesian Minister of Health Regulation Number 4 of 2019 concerning Minimum Service Standards in Health, every diabetes mellitus patient receives healthcare services through the community diabetes control program as a secondary prevention effort to reduce the risk of complications. One standard healthcare service for secondary prevention, which needs to be developed through engaging media at the Babakan Tarogong Public Health Center for Prolanis patients, is health education. Objective: To determine the effect of WhatsApp broadcast media on Prolanis patients knowledge about preventing the risk of diabetes mellitus complications. Methodology: This study uses a quantitative pre-experimental design in the form of a One-Group Pretest-Posttest Design. The population consisted of 16 Prolanis patients with diabetes mellitus, all of whom were included in the study sample. Analysis was performed using parametric statistics with the Paired t-test. Results: The WhatsApp broadcast media, Sawala Boga Aksi, was developed based on needs analysis and validated with very feasible scores: 94% from content experts and 93% from media experts. The average knowledge score of the target group before the intervention was 81.25, which increased by 16.25 to 97.50 after the intervention. The significance value (2-tailed) was 0.000 < 0.05. Conclusion: There is an effect of education through WhatsApp broadcast on Prolanis patients knowledge about preventing the risk of diabetes mellitus complications at the Babakan Tarogong Community Health Center.